Design analysis for a special serial - parallel manipulator - My, Chu Anh; Trung, Vuong Tien (Vietnam Journal of Science and Technology, 2016)
To reduce the downtime and optimize the use of energy and manpower, a serial - parallel manipulator is designed for transferring heavy billets for a specific hot extrusion forging process. To increase the structural rigidity and restrict the end-effector of the robot moving in direction parallel with the ground surface, parallel links are added in between serial links of the manipulator design. This modification of the structure must be considered in the modeling and analyzing. This paper addresses the kinematic modeling, the kinematic performance analysis and the strength analysis for the robot. With respect to the parallel links, the constraint equation is written and put together with the kinematic model. Based on the model formulated, the inverse kinematic, the transferring time, the reachable workspace, the dexterity, and the manipulability index of the robot are analyzed and discussed to demonstrate its kinematical performance. These results are important to assess the working capability and improve the parametric design for the robot. In addition, for verifying the end-effector design in terms of the strength and displacement, the stress distribution and the static deflection of the end-effector module are computed and analyzed by using the computer-aided finite element method (FEM)